Kompresi File Dokumen Menggunakan Algoritma Boldi-Vigna Codes - Siti Maria Br Pandia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
At this time, files of the DOCX type are widely used by people among office workers and also among students, a document file is a file that is used to store important files and then stored on a computer. it is also easy to search by typing the attribute or name created by the user. The size of a file that will be stored greatly affects storage space, which if the size of the file stored is large, the storage space must also be large, such as document files, the more content in a document, the larger the document size. The solution to overcome problems like this is to perform data compression techniques. Data compression aims to reduce a file size which can reduce the bit size in each document file, but does not eliminate the information data in it. By compressing, large data will be reduced in size so as to save storage space. In this study the algorithm used is the boldi-vigna codes algorithm, the compression results will benefit and storing document files will be easier.